What makes Gen Y and Z feel stressed, anxious and interested in doing social tourism when pandemic? - Rahmawati Rahmawati; Sri Langgeng Ratnasari; Tetra Hidayati; Ramadania Ramadania; Heru Kurnianto Tjahjono (Cogent Business & Management, 2022)
The pandemic leap continues and only makes things worse. Sharp criticism continues to pour in about what measures it can put in place to reduce the social crisis. Although some have accused the restrictions of being relaxed (lockdown), it does not improve human nature, which instinctively requires communication with partners, family, and co-workers. This study has a target to uncover the relationship between stress and anxiety on social tourism interest. We invited the 321 respondents to be surveyed online. The characteristics of the response involved cross-age, namely generations Y and Z (17 to 40~years) from 15 provinces in Indonesia. Structural Equation Modeling (SEM) applied to the AMOS program to interpret the data. Statistical tests found that stress and anxiety levels had no significant effect on social tourism interest. Other results prove an important difference if altruistic value increases social tourism interest significantly. From empirical moderation, altruistic value actually plays a significant role in the relationship between stress and anxiety levels in social tourism interest. The respondents have emotional resilience in the face of COVID-19. Finally, the novelty, contribution, and implications of the research is comprehensively disclosed. A follow-up agenda could investigate these findings in order to improve upon the limitations of the study.
Keywords: C38; D70; Z13; Z33; 650; COVID-19; SEM; Indonesia; Generation Y; generation Z; social tourism